Teacher Communication Patterns in the One Week One Book Program to Increase Motivation to Read Class X MA An-Najah I Karduluk - Faizatul Jannah; Agus Saifuddin Amin (al-Afkar, Journal For Islamic Studies, 2024)
Teacher communication patterns play an important role in triggering students' reading motivation. By creating certain communication patterns, it is easy for students to master the learning being taught. Therefore, this study focuses its study on how teacher communication patterns through the one week one book program in increasing student reading motivation by taking the case of class X MA An-Najah I. This research approach uses field research (Field reseach) with qualitative methods. Data collection techniques are carried out by interviews, observation and documentation. The research subjects were taken from 9 informants to check the validity of the data through the use of source trianggulation. The results of this study show that there is a one-way communication pattern applied at the An-Najah I Karduluk MA institution in explaining subjects and a two-way communication pattern in providing question and answer opportunities to students. There is also a pattern of multidirectional communication in giving group assignments to these students. So it can be concluded that the pattern of communication that occurs between teachers and students at the MA An-Najah I institution has an impact on 1) a good understanding for students of the explanation given, 2) providing positive feedback that makes it easier to measure the level of student understanding and 3) fostering interest and motivation in active learning from the students' own interpesronal.